Ejector powerplant system with natural working fluid - Berana, Menandro S.
This paper presents the potential application of ejector and the efficiency improvement it brings to powerplants that utilize low temperature renewable and recoverable heat sources. The ejector significantly increases the efficiency of the organic Rankine cycle (ORC) by increasing the turbine temperature drop which is made possible by the expansion, mixing and recompression processes in the ejector. The driving fluid in the ejector of the modified cycle is the high pressure liquid in the separator that is just circulated back to the evaporator in the ORC. Fundamental thermodynamic analysis of the novel ejector powerplant cycle was undertaken. Ammonia and propane, which are both natural working fluids, were used in the analysis. The analysis was limited by considering that the lowest pressure in the system must be higher than the atmospheric pressure to avoid vacuum leak. The calculation results showed that propane and ammonia can both give maximum efficiencies at different evaporator temperatures and fixed condenser temperatures in the range of 20-27 percent. At evaporator and condenser temperatures of 40 degrees and 30 degree celcius, respectively, ORC gives only 2.5 percent for the two working fluids while the ejector system gives 21.5 percent and 27.5 percent for ammonia and propane, respectively. The difference in efficiency reduces as the evaporator temperature increases. It has been shown that propane can give higher efficiencies and lower velocities in the ejector than ammonia at considerably lower evaporating temperatures, leading to more economical, safer and simpler design and operation. The ejector system with ammonia and propane as working fluids offers environment friendly power generation from low temperature sources at improved efficiency.
Keywords: Ejector; Powerplant; Propane; Ammonia; Organic Rankine cycle